The words of the semantic fields of law and religion in the work of David Son of Alavk "Canonical Code" - Dilbaryan, Narine (Bulletin of Yerevan University B: Philology, 2023)
In the Armenian literature of the XI-XII centuries, the book of laws "Canonical Code" compiled by the Monk David Son of Alavka occupies a special place. This most important work relating to legal thought and legislation in medieval literature is practically not studied from a linguistic point of view. Studying the lexical units of the semantic fields of law and religion in the “Canonical Code” by David Vardapet, we see that most of the roots and suffixes that form terms and concepts with the semantic meaning of law and religion are of Indo-European origin, they are productive even now in modern Eastern Armenian language. When compiling the "Canonical Code", David Son of Alavk used a number of sources - mainly the Bible, the works of Armenian chroniclers, philosophers and clergyman, as well as folklore materials, in which the national system of moral values, ancient beliefs and prejudices are clearly expressed.            The language of the Code, as Vardan Areveltsi, one of David's younger contemporaries, rightly noted, is "easily accessible." It occupies an intermediate position between Classical Armenian and Middle Armenian, which makes it possible to identify the process of transition from one literary language to another. This character of the language is due to the fact that, although David lived and worked in the Middle Ages, he received a high spiritual education, was a clergyman, was awarded the title of teacher-vardapet, and the language of education and science was the Ancient Armenian language.            The semantic fields of religion and law did not have a clear borders in the Middle Ages. David the legislator in his book mentioned in detail about human sins and virtues. In the case of analyzing such words, it is difficult to determine in which semantic field they can be included, because, for example, sins and crimes are equally unacceptable and punishable by both the church and the court. The semantic subgroup containing such concepts can be conditionally called "sin and crime". In this study, the main units of the semantic field of religion and law were considered by their etymology, the Indo-European units that form the core of the vocabulary were identified, then borrowings and hybrid formations. 46% of the units studied in these two semantic fields are native words, 25% are hybrids (with combinations of an Indo-European root or suffix and a borrowed root or suffix), 20% are Iranian, 4% are Greek and Syriac, and 1% are Akkadian.            The code, compiled by David Son of Alavk, shows that the Armenian language in the Middle Ages already had a rich and multifaceted legal and religious vocabulary.
Keywords: David Son of Alavk; vocabulary; semantic fields of law and religion; etymology; Indo-European roots; borrowings; hybrid formations